Soil fertility and upland rice yield after biochar application in the Cerrado - Petter, Fabiano André; Silva, Mellissa Ananias Soler da; Madari, Beáta Emoke; Carneiro, Marco Aurélio Carbone; Carvalho, Márcia Thaís de Melo; Pacheco, Leandro Pereira; Marimon Júnior, Ben Hur (Pesquisa Agropecuaria Brasileira, 2012)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>The objective of this work was to evaluate the effect of biochar made from Eucalyptus on soil fertility, and on the yield and development of upland rice. The experiment was performed during two years in a randomized block design with four replicates, in a sandy loam Dystric Plinthosol. Four doses of NPK 05‑25‑15, annually distributed in stripes (0, 100, 200 and 300 kg ha‑1), and four doses of biochar (0, 8, 16 and 32 Mg ha‑1), applied once in the first year – alone or with NPK – were evaluated. In the first year, biochar positively affected soil fertility [total organic carbon (TOC), Ca, P, Al, H+Al, and pH], at 0–10 cm soil depth, and it was the only factor with significant effect on yield. In the second year, the effect of biochar diminished or was overcome by the fertilizer. TOC moved down in the soil profile to the 0–20 cm depth, influencing K availability in this layer. In the second year, there was a significant interaction between biochar and the fertilizer on plant growth and biomass dry matter accumulation.